Some Technological Properties of Lactic Acid Bacteria Isolated from Dahi and Datshi, Naturally Fermented Milk Products of Bhutan - Shangpliang, H. N. J.; Sharma, Sharmila; Rai, Ranjita; Tamang, Jyoti P. (Frontiers in Microbiology, 2017)
Dahi and datshi are common naturally fermented milk (NFM) products of Bhutan. Population of lactic acid bacteria (LAB) in dahi (pH 3.7) and datshi (pH 5.2) was 1.4 x 107 and 3.9 x 108 cfu/ml, respectively. Based on 16S rRNA gene sequencing isolates of LAB from dahi and datshi were identified as Enterococcus faecalis, E. faecium, Lactococcus lactis subsp. lactis. LAB strains were tested for some technological properties. All LAB strains except E. faecalis CH2:17 caused coagulation of milk at both 30°C for 48 h. Only E. faecium DH4:05 strain was resistant to pH 3. No significant difference (P>0.05) of viable counts was observed in MRS broth with and without lysozyme. All LAB strains grew well in 0.3 % bile showing their ability to tolerate bile salt. None of the LAB strains showed >70 % hydrophobicity. This study, being the first of its microbiological analysis of the NFM of Bhutan, has opened up to an extent of research work that gives a new insight to the products.